Immersive Real-Acting Virtual Aquarium with Motion Tracking Sensors - Yoon-Seok Choi; Soonchul Jung; Jin-Sung Choi; Bon-Ki Koo; Won-Hyung Lee (International Journal of Distributed Sensor Networks)
We realized a real space-based virtual aquarium equipped with a multiview function that provides images for users and audiences at the same time through motion tracking sensors. A virtual reality system needs more natural and intuitive interfaces so as to enhance users' immersion. We attach markers on users and camera devices in a real space designed in the one-to-one size as the virtual space to trace user and camera motions, which is reflected in real time to generate virtual world images. These images are transmitted to the user's immersing image devices. Also, the system allows audiences to share experiences by providing them with virtual synthetic images from a third-person perspective including a user after taking the user in the real space with a camcorder on which motion tracking markers are attached. For this, the system provides the functions of marker-based motion tracking with sensors, recognition of user's motions, real-time actual image rendering, and multiview to realize a system to simulate more intuitive and natural virtual space interactions, which can be used for the construction of motion-based realistic/experiencing systems, which increasingly attract interest.